Innovative development of the energy service enterprise as an object of management - BRYCH, VASYL; KUPCHAK, VOLODYMYR; BORYSIAK, OLENA; HUHUL, OKSANA; HALYSH, NATALIYA; FURSA, TETIANA; SOKOL, MARIANA (The journal of contemporary issues in business and government, 2021)
The understanding of the peculiarities of innovations and innovative development of the energy service enterprise has been outlined in the article. The essence of the concept of "innovation" has been determined. To improve approaches to innovative development of the enterprise, it has been proposed to consider innovation as a result (product, process, service). This article is aimed at solving the problems of the energy service market, in particular the management of enterprises that provide production processes in the power industry to improve the technical equipment of labor, the rational organization of the workplace. The article presents the features of the formation of energy efficiency management strategy of enterprises using a comprehensive assessment of the internal and external environment based on sustainable development and practical approach combined with a comprehensive interpretation of the concept of energy efficiency management strategy of enterprises. The study takes into account the specificity through the emphasis on the system of areas (directions) to be managed in the framework of strategic management and provides references to the main characteristics associated with existing approaches to target effects and systemic, comprehensive approach to strategic management in this sphere. A significant role is given to human resources in the mechanism of stimulating and motivating the energy efficiency of the enterprise, which is manifested in situations when the production process is energy-consuming or when the enterprise is a supplier of energy resources. It is in such areas of activity that every employee, regardless of management level, must understand the reasons for specific management actions, how their result will affect the results of work, and what will be the reward for it.